2022
DOI: 10.20870/oeno-one.2022.56.2.5432
|View full text |Cite
|
Sign up to set email alerts
|

Legacy of land-cover changes on soil microbiology in Burgundy vineyards (Pernand-Vergelesses, France)

Abstract: Present-day soil physicochemical characteristics, land use/land cover (LULC), and field management practices are commonly recognised as the main drivers shaping archaeal/bacterial and fungal communities in vineyard soils. Few studies have investigated the legacy of past land uses on soil microbial biodiversity, yet anthropogenic disturbances have already been proven to affect soil characteristics over decades. In this study, we explore the possibility of long-lasting impacts of forest-to-vineyard conversion on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…A recent study led by Marcel G. A. van der Heijden at Agroscope and the University of Zürich (Edlinger et al 1 ) found that AMF diversity was lower in cereal-producing farmland soils than in grassland soils, because AMF are negatively impacted by agricultural practices such as plowing or the use of fungicides and inorganic fertilizers 1 . Other studies observed similar reductions in microbial and fungal diversity in the soils of other agricultural systems, such as vineyards 2 , 3 , orchards 3 , and arable crops 4 . Most modern crop plants have not been bred with this symbiotic relationship with AMF in mind, and thus are only inefficiently colonized by AMF 1 .…”
supporting
confidence: 56%
See 1 more Smart Citation
“…A recent study led by Marcel G. A. van der Heijden at Agroscope and the University of Zürich (Edlinger et al 1 ) found that AMF diversity was lower in cereal-producing farmland soils than in grassland soils, because AMF are negatively impacted by agricultural practices such as plowing or the use of fungicides and inorganic fertilizers 1 . Other studies observed similar reductions in microbial and fungal diversity in the soils of other agricultural systems, such as vineyards 2 , 3 , orchards 3 , and arable crops 4 . Most modern crop plants have not been bred with this symbiotic relationship with AMF in mind, and thus are only inefficiently colonized by AMF 1 .…”
supporting
confidence: 56%
“… 1 and Quiquerez et al . 2 show the critical and broad importance of healthy soil and of the abundance and diversity of microorganisms in the soil for future agricultural systems. Future research could focus on agricultural methods that can improve the beneficial symbiosis between microorganisms such as AMF in the soil and plants while maintaining yields, with the possibility of partially replacing phosphorus-based fertilizers with AMF-mediated phosphorus uptake.…”
mentioning
confidence: 99%
“…Differences in vineyard management can modify microbial communities [212] and, by this means, have an impact on the type and quantity of ecosystem services provided. Some studies suggest that, together with geographical location and climate, vineyard management is related to the diversity of yeast taxa present in grapes [74,103,213,214]. In terms of bacterial composition, vineyard management seems to have a direct impact on the composition of its communities [162,215].…”
Section: Vineyard Management and Microbiota Ecosystem Servicesmentioning
confidence: 99%